2022
DOI: 10.3390/nu14142857
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Knowledge, Attitudes and Practices of Healthy Eating: Findings of Qualitative Interviews among Hong Kong Families

Abstract: To tackle unhealthy eating among adolescents, it is crucial to understand the dietary knowledge, attitudes, and practices (KAP) on which adolescent eating habits are based. This qualitative study identifies the gaps in KAP by exploring what Chinese adolescents know, perceive, and practice regarding healthy eating to better inform targeted interventions for this important health problem. Parent–adolescent dyads were purposively sampled based on, for example, the dietary intake, age, and gender of the adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 42 publications
2
18
0
1
Order By: Relevance
“…During the qualitative component of the study, students discussed the wider influences of their food choices whilst on campus, including socio-cultural factors such as peer influence, nutritional quality of foods, time and location, price, and taste. These findings were consistent with previous research that found university students to consume unhealthier foods knowingly due to the convenience, lower price point and peer influence [ 24 ]. Additionally, students reported that taste preferences had a large impact on their food choices whilst on campus as they were less likely to consume healthier foods which were less appealing.…”
Section: Discussionsupporting
confidence: 93%
“…During the qualitative component of the study, students discussed the wider influences of their food choices whilst on campus, including socio-cultural factors such as peer influence, nutritional quality of foods, time and location, price, and taste. These findings were consistent with previous research that found university students to consume unhealthier foods knowingly due to the convenience, lower price point and peer influence [ 24 ]. Additionally, students reported that taste preferences had a large impact on their food choices whilst on campus as they were less likely to consume healthier foods which were less appealing.…”
Section: Discussionsupporting
confidence: 93%
“…explained the research aim to the families at the beginning of the interview and conducted the interview using a semi-structured interview guide ( Supplementary Materials Document S1 ). The interview guide was developed from the KAP framework that has been used in previous studies [ 19 , 21 ]. Questions were first directed to the adolescents to elicit their perspectives before supplementation by the parents.…”
Section: Methodsmentioning
confidence: 99%
“…1,[6][7][8] Another qualitative study reported that adolescents did not consider health as the top priority when making food choices; those with fewer healthy eating habits had a poor perception of health risk. 7 Unhealthy eating habits in adolescents were also affected by peer influence, lack of knowledge of and easy access to healthy food, and the perception that 'healthful food is more expensive'. 1,7 Although the Department of Health in Hong Kong 9 has recommended food intake for school children is in the ratio of 3:2:1 (grains:vegetables:meat and its alternatives) by volume, the evident proportion of school-aged children with overweight or obesity reflects the serious problem of unhealthy food consumption young students.…”
Section: Introductionmentioning
confidence: 99%
“…7 Unhealthy eating habits in adolescents were also affected by peer influence, lack of knowledge of and easy access to healthy food, and the perception that 'healthful food is more expensive'. 1,7 Although the Department of Health in Hong Kong 9 has recommended food intake for school children is in the ratio of 3:2:1 (grains:vegetables:meat and its alternatives) by volume, the evident proportion of school-aged children with overweight or obesity reflects the serious problem of unhealthy food consumption young students. 10 The latest local data showed that, in the annual school year of 2019/2020, the percentage of overweight and obesity of primary school and secondary school students is 19.0% and 21.3%, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation